Principal approaches and achievements in studying race composition of wheat stem rust - A. S. Rsaliyev; Sh. S. Rsaliyev (Вавиловский журнал генетики и селекции, 2019)
Wheat stem rust caused by the biotrophic fungus Puccinia graminis f. sp. tritici is a dangerous disease that seriously damages the economics in many countries of the world. The review contains information about epidemics of wheat stem rust and causes of their emergence worldwide. Recently wheat stem rust epidemics have been recorded in the northern regions of Kazakhstan and on the territories adjacent to Omsk Region of Russia. It has been shown that severe wheat stem rust epidemics occur mainly due to the emergence of new virulent races of the disease agent and to growing susceptible wheat cultivars. New methods of studying the race composition of the fungus are described as well as the use of the previous and current diﬀerential sets for race determination of P. graminis f. sp. tritici. The results of developing molecular markers and assessing their eﬀectiveness in studying stem rust races are presented. Wheat stem rust races dominant in major grain-growing countries of the globe and their typical peculiarities are described. The paper contains information on identifcation of race Ug99 and of its variations including data on areas of their dissemination and on their virulence to Sr-resistance genes. The existence and emergence of other races of the agent potentially dangerous for commercially important genes for stem rust resistance is also described. Currently in nature strongly virulent races of P. graminis f. sp. tritici are circulating with wide geographical coverage and their virulence is absolutely diﬀerent from the virulence of race Ug99. Historical and modern data on studying the race composition of the pathogen in Kazakhstan are summarized. It is stated that the use of the old standard diﬀerential set and an incomplete North American system of race nomenclature in experiments prevents measuring similarity between Kazakhstani races and the worldwide known races of the pathogen. It has been shown that there is a need to continue studies on the intraspecies structure of the disease agent’s population in Kazakhstan with the use of the modern diﬀerential set, on determination of race composition and ways of emergence of new races potentially dangerous for commercial wheat varieties.